Four cases of transcatheter aortic valve implatation - Yin-Xia HUANG; Min LI; Xin-Hao CHEN; Xing-You LIU; Ji-Gang HE (Yixue xinzhi zazhi)
From 2018 to 2020, four patients with aortic valve disease in the First People's Hospital of Yunnan Province underwent transcatheter aortic valve implantation (TAVI). Three of the patients had severe aortic stenosis, and one patient had severe aortic regurgitation. The valve-in-valve method was used for the patient with severe aortic regurgitation. The operations for all 4 patients went smoothly and they were able to mobilize out of bed 10 hours after surgery. Five days postoperatively, all relevant indicators were satisfactory and they were able to be discharged. All patients had no discomfort on follow-up up to October 2020. It can be seen from these four patients that TAVI surgery is highly recommended for patients with aortic stenosis or other eligible dysfunctions which are assessed to be a risk for older patients, and the transfemoral approach is preferred.